Can Cognitive Assessments be Fun? A Review of Playful Mobile Applications to Assess Cognitive Health - Polzer, Nina; Gewald, Heiko (Asian Interdisciplinary and Sustainability Review, 2019)
Due to the increasing average lifespan in economies all over the world the proportion of older members of society increases to grow. Older people are specifically prone to a cognitive decline due to Alzheimer’s Disease or related forms of Dementia. Although there is currently no medical cure available, early detection of Dementia would enable earlier treatment with medication to postpone the outbreak which enables the person to have a longer self-sustained living. The application of new information and communication technology is a growing body of research this area. Initial results indicate that serious games and playful mobile applications are able to improve cognitive and physical health areas of people who are affected by Alzheimer’s Disease or other Dementias. However, less is known about their potential to detect the cognitive decline. This paper provides a structured overview of published to employ mobile applications with playful elements to assess the cognitive health of the user. Existing applications are identified and analyzed for the specific type of cognitive stimuli they are addressing.